A test of a sun glint correction method for the near-3.9 μm channels of the FengYun-3D Hyperspectral InfraRed Atmospheric Sounder (HIRAS). Issue 10 (2nd October 2020) - Wang, Liwen; Niu, Zeyi; Zhang, Banglin; Tang, Fei; Liang, Jiahao
ABSTRACT: The Hyperspectral InfraRed Atmospheric Sounder (HIRAS), the first Chinese sun-synchronous hyperspectral infrared sounder onboard FengYun 3D (FY-3D), was launched on 15 November 2017. It will play a significant role in improving forecast accuracy of numerical weather prediction (NWP) systems. However, sun glint effects on the FY-3D HIRAS 3.9 μm channels cannot be currently estimated by radiative transfer models. In this study, a new method for quantifying sun glint effects has been developed through a cubic fitting relationship between sun glint angles and the observed brightness temperature minus simulated brightness temperature ( O − B ) after bias correction. The results show that the brightness temperatures of channel 2275 (2550 cm −1 ) are higher over the ocean between 40°S and 40°N within areas of sun glint angle less than 40°; in these regions, O − B values can reach 10 K during the daytime. Daytime global mean clear-sky O − B biases from channel 2035 (2400 cm −1 ) to channel 2275 (2550 cm −1 ) increase gradually from 0 to 2.5 K. In contrast, daytime O − B biases after sun glint correction are within ±0.2 K, indicating that the corrected radiances are suitable to be assimilated into NWP systems.